Mitochondrial Uncoupling Proteins (UCP1-UCP3) and Adenine Nucleotide Translocase (ANT1) Enhance the Protonophoric Action of 2,4-Dinitrophenol in Mitochondria and Planar Bilayer Membranes - Žuna, Kristina; Jovanović, Olga; Khailova, Ljudmila S; Škulj, Sanja; Brkljača, Zlatko; Kreiter, Jürgen; Kotova, Elena A; Vazdar, Mario; Antonenko, Yuri N; Pohl, Elena E (Biomolecules, 2021)
2,4-Dinitrophenol (DNP) is a classic uncoupler of oxidative phosphorylation in mitochondria which is still used in "diet pills", despite its high toxicity and lack of antidotes. DNP increases the proton current through pure lipid membranes, similar to other chemical uncouplers. However, the molecular mechanism of its action in the mitochondria is far from being understood. The sensitivity of DNP's uncoupling action in mitochondria to carboxyatractyloside, a specific inhibitor of adenine nucleotide translocase (ANT), suggests the involvement of ANT and probably other mitochondrial proton-transporting proteins in the DNP's protonophoric activity. To test this hypothesis, we investigated the contribution of recombinant ANT1 and the uncoupling proteins UCP1-UCP3 to DNP-mediated proton leakage using the well-defined model of planar bilayer lipid membranes. All four proteins significantly enhanced the protonophoric effect of DNP. Notably, only long-chain free fatty acids were previously shown to be co-factors of UCPs and ANT1. Using site-directed mutagenesis and molecular dynamics simulations, we showed that arginine 79 of ANT1 is crucial for the DNP-mediated increase of membrane conductance, implying that this amino acid participates in DNP binding to ANT1.
Keywords: Mitochondrial ADP, ATP Translocases; Mitochondria, Liver; jaterní mitochondrie; Animals; artificial membranes; Lipid Bilayers; membránové potenciály; lipidové dvojvrstvy; proton conductance; membrane potential; mitochondrial uncoupler; Mice; molecular dynamics simulations; mitochondriální odpřahující proteiny; myši; mitochondriální ADP/ATP-translokasy; Mitochondrial Uncoupling Proteins; 2,4-Dinitrophenol; protonophore; krysa rodu Rattus; zvířata; Rats; 2,4-dinitrofenol; Membrane Potentials